Role of point of care lung ultrasound in neonatal respiratory distress in comparison with chest X-ray-a clinico-radiological evaluation - ., Manusha; Bhushan, Shashi; Aneja, Satinder; Gupta, Amit; Sabhikhi, G. S. (International Journal of Contemporary Pediatrics, 2022)
Background: The use of ultrasound for immediate management of life-threatening conditions is one among the main changes of these last decades. Lung ultrasound has become more and more popular in the first decade of the 21st century, both in neonatal and in paediatric age groups. The lung ultrasound may be tool in differential diagnosis of respiratory distress in newborns. Aims and objectives: To assess diagnostic role of point of care lung ultrasound in neonates presented with respiratory distress and analyse the possibility of initiating management protocol based on lung ultrasound finding. Methods: Present non-randomized study-a hospital based analytical cross-sectional study was carried out in 60 patients with respiratory distress for a period of 18 months (January 2020-30 June 2021). Neonates suffering from respiratory distress (Pulmonary cause with Downe’s score >4) were included. Routine investigations, lung USG and chest x-ray examination was recorded. Detailed perinatal history were obtained. Results: Mode of delivery was LSCS among 38.3% and vaginal delivery among 61.7% subjects. The mode of respiratory support was CPAP among 33.3% and ventilator among 66.7% subjects. Mean birth weight of the study population was 2003.51±767.35 grams. Final diagnosis of the present study shows that majority of neonates had respiratory distress syndrome (38.33%) followed by birth asphyxia with respiratory distress (28.33%) followed by TTNB (11.66%). A total of 25.0% neonates had Downes score 4, 16.7% had 5, 25.0% had 6, 26.7% had 7 and 6.7% neonates had 8 score. X-ray findings showed sensitivity 56.67% and positive predictive value 100% were observed. On the basis of USG findings, 93.22% sensitivity and positive predictive value 98.21% were observed. Conclusions: Lung ultrasound is a non-invasive, bedside and repeatable method that could improve the management of neonatal respiratory distress. Neonatal lung ultrasound is a useful predictor of the need for intubation over chest x-ray. Combined lung consolidation, pleural line abnormalities and absence of A line findings were the most specific lung ultrasound findings in RDS which were present among majority of the patients.